LEVEL THE INSERTION LEVELS OF WOMEN PHYSIOTHERAPIST INTO SPORTING PHYSIOTHERAPY AND RESPECTIVE PROFESSIONAL SELECTION CRITERIA IN CLUBS OF RIO DE JANEIRO. (Fiep Bulletin - online, 2014)
The physiotherapy which is an area from health whose objective is rehabilitate individuals functionally, on which the Sporting physiotherapy aim at on the prevention, the diagnostic , the treatment and the return of the athlete to the sport with thorough rehabilitation. The present study had the purpose of explore the incidency of woman physiotherapist in the marketplace of work from Sporting Physiotherapy with its due selection professional criteria. The study has as relevance to do best clear the topic which is little explored, revising conceptions of assessment and selection of choicing of women physiotherapists and to open the tread for added multi-skilled on area from sporting physiotherapy sporting by women, picking roads for a equality professional. The sample from research was off the rack by means of choice intentional, for convention into four associations of soccer professional from city of the Rio de Janeiro, which are on the first division in the year of 2007 and that has into the medical department a sector of physiotherapy. It has been realized interviews by using an itinerary of eleven questions semi - opened. The outcomes obtained have been the criteria of selection from the physiotherapists on the associations occur for indication of another professionals and that no exists preconception in relation to the c woman into the sport, within the moment what the she works with the amateur sport, where no wonder sense a country's number of women acting. It was concluded that at fact from she hires be off the rack from one side to the other indication the tendency from a major difficulty for insertion from woman on Sporting Physiotherapy and that the prejudice again exists into the professional sport, where is about a requirement the professional be man.
Keywords: Woman; Sporting Physiotherapy; selection professional